Social Barriers to Effective Communication in Old Age - Sanecka, Anna (Journal of Education Culture and Society, 2020)
Some communication barriers apply particularly to elderly people. The social barriers to effective communication in old age are the barriers caused by stereotypes of old age/elderly people and the barriers arising from limitations in using mass communication by seniors. Stereotypes of old age/elderly people embrace views regarding old people’s communication skills and the ideas about the correct way of communication with them. Therefore the communication problems of old people are correlated with the little and poor communication processes they are participating in. This seems to be a result of impetuses of poor quality sent to seniors by their communication partners. Not only face to face communication but also mass communication is very important for the elderly population. Therefore limitations in using new technologies and new communication channels as well as a limited presence in the mass media of content created by seniors and for seniors have an impact on their life, their well-being, and their interpersonal relationships. These problems are especially important when we faced with the ever growing population of elderly people.